People think about what is true for conditionals, not what is false: only true possibilities prime the comprehension of "if" - BYRNE, RUTH MARY JOSEPHINE (My University, 2009)
We report the results of two priming experiments that examine the comprehension of conditionals--for example, "if there are apples then there are oranges"--and biconditionals--for example, "if and only if there are apples then there are oranges". The first experiment showed that participants read a biconditional faster when it was primed by a true possibility, "there were apples and there were oranges" than when it was primed by a false possibility, "there were no apples and there were oranges"; a conditional was primed equally by both possibilities. The second experiment showed that participants read the negated-antecedent conjunction faster when it was primed by a conditional than when it was primed by a biconditional; the affirmative conjunction was primed equally by both connectives. The experiments show that (a) when people understand "if A then B", they access the true possibilities, "A and B", and "not-A and B", and (b) when they understand "if and only if A then B" they access "A and B", but they do not access "not-A and B". We discuss their implications for current theories of reasoning.
PUBLISHED
Keywords: Psychology